2021
DOI: 10.1002/ueg2.12057
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in acute pancreatitis with persistent organ failure is determined by the number, type, and sequence of organ systems affected

Abstract: Background Persistent organ failure (POF) is the strongest determinant of mortality in acute pancreatitis (AP). There is a paucity of data regarding the impact of different POF attributes on mortality and the role of different characteristics of systemic inflammatory response syndrome (SIRS) in the risk of developing POF. Objective We aimed to assess the association of POF dynamic features with mortality and SIRS characteristics with POF. Methods We studied 1544 AP subjects prospectively enrolled at 22 interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…15 However, organ failure remains to be a stronger predictor of mortality than local complications (peri-pancreatic fluid collections and necrosis) and influences the length of hospital stay. 15,21,22 Multiple scoring systems have been developed based on clinical, biochemical, and imaging assessments in an attempt to predict the severity and prognosis of AP. 20,23,24 Most of the models are based on data available from two points in time (i.e., at admission and 48 h), which makes them impractical to use in a triage setting.…”
Section: Discussionmentioning
confidence: 99%
“…15 However, organ failure remains to be a stronger predictor of mortality than local complications (peri-pancreatic fluid collections and necrosis) and influences the length of hospital stay. 15,21,22 Multiple scoring systems have been developed based on clinical, biochemical, and imaging assessments in an attempt to predict the severity and prognosis of AP. 20,23,24 Most of the models are based on data available from two points in time (i.e., at admission and 48 h), which makes them impractical to use in a triage setting.…”
Section: Discussionmentioning
confidence: 99%
“…The main causes of death in the early phase of severe AP are systemic inflammation and organ failure. In patients with persistent multiple organ failure, the mortality rate will be > 30% [ 30 ]. Although the difference between the two groups was not statistically significant at α = 0.05, it is still intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…3 Specifically, multisystem organ failure ([MSOF]; organ failure involving two or more vital organs) represents the most terminal stage of systemic complications and is the main driver of mortality in AP. 2,4 Obesity and alcoholic etiology-present in 30%-50% of AP cohorts-have been examined as potential risk factors for MSOF in a few studies. 5,6 However, previous studies have generated conflicting results: some even suggested the "obesity paradox," implying that obesity has protective effects in severe AP, 7 while others found that obesity does not increase the risk of organ failure.…”
Section: Introductionmentioning
confidence: 99%
“…While there has been substantial progress in the management of local complications, such as acute fluid and necrotic collections in AP, there is currently no effective treatment to mitigate organ failure, a potentially fatal systemic complication of AP 3 . Specifically, multisystem organ failure ([MSOF]; organ failure involving two or more vital organs) represents the most terminal stage of systemic complications and is the main driver of mortality in AP 2,4 …”
Section: Introductionmentioning
confidence: 99%